Porous Silicon Bragg Reflector/Carbon Dot Hybrids: Synthesis, Nanostructure, and Optical Properties - Massad-Ivanir, Naama; Bhunia, Susanta Kumar; Jelinek, Raz; Segal, Ester (Frontiers in Chemistry, 2018)
Carbon dots (C-dots) exhibit unique fluorescence properties, mostly depending upon their physical environments. Here we investigate the optical properties and nanostructure of Carbon dots (C-dots) which are synthesized in situ within different porous Silicon (PSi) Bragg reflectors. The resulting hybrids were characterized by photoluminescence, X-ray photoelectron, and Fourier Transform Infrared spectroscopies, as well as confocal transmission electron microscopy. We show that by tailoring the location of the PSi Bragg reflector photonic bandgap and its oxidation level, the C-dots emission spectral features can be tuned. Importantly, enhancement of the fluorescence emission is achieved when the high reflection band of the PSi host overlaps with the confined C-dots' peak wavelength and the PSi matrix is thermally oxidized at mild conditions. These phenomena are observed for multiple compositions of PSi Bragg reflectors/C-dots hybrids.